Through the eyes of envy: how social anxiety fuel risky appearance management behaviors - Chen Yang; Xue Yang; Yan-Qian Liu (BMC Psychology)
Abstract Background This study examined the role of envy in socially anxious situations and its impact on risky appearance management behaviors (AMBs). The primary goal was to determine whether envy mediates the relationship between state social anxiety and non-routine AMBs. Methods Three experiments were conducted. Study 1 (Study 1a: n = 140; Study 1b: n = 162) induced social anxiety using two different paradigms, revealing that individuals in a socially anxious state reported increased envy, leading to a higher willingness to engage in risky skin management, diet pill use, and cosmetic surgery compared to the control condition. Study 2 (n = 99) directly manipulated envy and found that participants primed with envy were more prone to participating in non-routine AMBs than those in a neutral condition. Results Overall, the findings showed that social anxiety triggered heightened envy, which mediated the association between state social anxiety and non-routine AMBs. Furthermore, envy also exerted a direct influence on these behaviors. Conclusions The study enhances our comprehension of the interplay between social anxiety and envy, providing a foundation for future exploration into how these emotions intertwine and shape both mental health and risk behaviors. Concretely, our findings uncover various avenues for exploring how social anxiety interacts with distinct emotions, impacting individuals’ psychological and behavioral well-being.